Sense-Making Of Shariah Digital Economy Among Muslim Micro-Entrepreneurs: A Qualitative Case Study Of Mandailing Natal - Jureid; Anjur Perkasa Alam; Asmawarna Sinaga; Mufti Fahrizal Harahap; Hamdanil (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Introduction: The development of the Shariah digital economy presents both opportunities and challenges for Muslim micro and small enterprises (MSMEs), particularly in interpreting Shariah principles in the digital era. This study aims to explore the sense-making process of Muslim MSME actors in Mandailing Natal in understanding and implementing Shariah-compliant digital economic practices. Methods: A qualitative interpretive case study approach was employed, involving some of active MSME informants through in-depth interviews, participatory observation, and documentation of digital Shariah practices. Findings indicate that Shariah compliance in digital practices is pragmatic, adaptive, and contextual, involving negotiation between technological efficiency and religious values, as well as dual legitimacy from formal authorities and personal experience. Results: The Results highlight the critical role of actor sense-making in constructing subjective understanding of complex and often ambiguous Shariah principles. Conclusion and suggestion: Theoretically, this research extends the literature on Islamic digital economy and Shariah fintech by emphasizing the interpretive social construction of Shariah compliance. Practically, the findings provide guidance for developing digital platforms, Shariah digital literacy programs, and collaborations between regulators and religious authorities to enhance inclusion and sustainability of Muslim MSMEs